THE APPLICATION OF PRINCIPAL LEARNING LEADERSHIP IN IMPROVING TEACHER PROFESSIONALISM AT BRODER KANISIUS PONTIANAK ELEMENTARY SCHOOL - Atawolo, Benediktus Gole; Hartoyo, Agung; Aswandi (Institut of Shanti Bhuana, 2023)
This study describes the application of principal learning leadership in increasing teacher professionalism at Brother Kanisius Elementary School, Pontianak. This research is descriptive research with a qualitative approach. The subjects of this research were school principals and teachers. Observation, interviews and documentation were carried out for data collection. Data analysis goes through stages: reduction, display, and conclusion. The data validity technique uses technical triangulation and data source triangulation. The results of the study show that the application of the Principal's learning leadership in improving teacher professionalism in the Brother Kanisius Pontianak Elementary School, namely: (1) The effectiveness of the Principal's learning leadership in building and maintaining the school vision at SD Brother Kanisius Pontianak is perfect and practical. The Principal is always committed and guided by the school's vision in managing and leading the school. (2) The Principal in leading the learning community, which has an influence on the professionalism of teachers at the Brother Kanisius Elementary School in Pontianak, has been very good with the improvement in the performance of the teaching and education staff at the school as well as the achievements achieved by students both academically and non-academicly. (3) The Principal's learning leadership in using data and monitoring the curriculum when making decisions in learning at the Brother Kanisius Elementary School in Pontianak has been carried out effectively, and the results are excellent. The school principal has developed an academic supervision program to increase teacher professionalism, conduct academic supervision of teachers using appropriate supervision approaches and techniques, and assess and follow up on supervision activities. (4) Obstacles in implementing the Principal's learning leadership have been overcome by collaborating with the entire school community and related agencies.